2015
DOI: 10.1007/s11244-015-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ni Species Distribution on the Effect of Ce as a Promoter in C2-ODH Reaction

Abstract: The aim of work was to analyse and discuss the effect of cerium on the catalytic behaviour of different types of nickel species in the oxidative dehydrogenation of ethane. Ni-Al and Ni-Ce-Al catalysts were prepared from cerium nitrate and nickel nitrate or nickel acetate as a precursor. As-prepared materials were characterized by using of XRD, DR UV-Vis spectroscopy and H 2 -TPR. It was found that the addition of cerium affects both the reducibility of nickel species and the population of nickel species. First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…They also reported that the structured systems show higher ethene productivity than the powder catalysts and that the catalytic features of the structured systems depend on the calcination temperature of the material . More recently, we reported that the distribution of Ni species and the catalytic behavior of Ni/Al 2 O 3 catalysts could also be affected by the type of nickel precursor (nickel nitrate vs nickel acetate) and by the Ce–Ni interaction . The results showed that Ni/Al 2 O 3 catalysts prepared by impregnation of alumina with nickel acetate contain higher relative populations of active small and dispersed NiO species, while the catalysts prepared by impregnation of alumina with nickel nitrate contain less active but more selective Ni­(T d ) species .…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…They also reported that the structured systems show higher ethene productivity than the powder catalysts and that the catalytic features of the structured systems depend on the calcination temperature of the material . More recently, we reported that the distribution of Ni species and the catalytic behavior of Ni/Al 2 O 3 catalysts could also be affected by the type of nickel precursor (nickel nitrate vs nickel acetate) and by the Ce–Ni interaction . The results showed that Ni/Al 2 O 3 catalysts prepared by impregnation of alumina with nickel acetate contain higher relative populations of active small and dispersed NiO species, while the catalysts prepared by impregnation of alumina with nickel nitrate contain less active but more selective Ni­(T d ) species .…”
Section: Introductionmentioning
confidence: 77%
“…The fact that the presence of Ce as a promoter increases the activity of Ni/Al 2 O 3 catalysts is in agreement with previously reported results. 23,26 Nevertheless, this difference in W/F ratios (the change in the activity) obtained for Ni/Al 2 O 3 and Ni−Ce/Al 2 O 3 catalysts calcined at the same temperature decreased with an increasing value of calcination temperature. All these conclusions are the same as those described based on Figure 7.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations